Improving the quality of matric learner performance in mathematics and science in Gauteng - Ngobese, Constance Nompumelelo (My University, 2014)
The foremost argument of this research is that the quality of matric learner performance in mathematics and science is poor. The objective of the research is to investigate the factors leading to poor performance in mathematics and science at matric level in Gauteng, South Africa. The research seeks to validate whether or not decision-making, policy and planning contribute to poor learner performance. Five documents addressing mathematics and science education matters were analyzed. Six candidates were interviewed to determine the causes of poor performance in mathematics and science at matric level in Gauteng and how the quality of learner performance could be improved. The findings confirmed that the quality of passes in mathematics and science is indeed poor and showed that the National Policy on Promotion and Progression Requirements Grades R-12 in particular contributes to this poor quality of learner performance. They also confirmed that poor decision-making at strategic level and poor planning are also contributors towards poor learner performance. Scenario planning, as a strategizing foresight tool, was employed to create the Gauteng scenarios for mathematics and science education in 2022. A recommendation is made that the GDE should use these scenarios as learning tools when preparing for the future and to improve their planning and decision-making processes.
Thesis (M.M. (Public Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: Mathematics; Science; Study and teaching; Matric; Learner performance; South Africa; Educational planning